White Vanishing Rethinking Australia's Lost-in-the-Bush Myth - Tilley, Elspeth (Amsterdam : Editions Rodopi, 2012)
The story of the vulnerable white person vanishing without trace into the harsh Australian landscape is a potent and compelling element in multiple genres of mainstream Australian culture. It has been sung in "Little Boy Lost," brought to life on the big
Description based upon print version of record.
Keywords: Myth, Stories; Myth; Popular culture -- Australia; Australian literature -- History and criticism; Motion pictures -- Australia -- History and criticism; Missing children in literature -- Australia; Missing children in art -- Australia; Missing persons -- Australia; Discourse analysis, Narrative -- Australia; Australia -- Social life and customs; Australia -- Civilization; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Electronic books